Phase-field modelling of mechanical wave propagation in polycrystalline materials: Validation study. (1st February 2023) - Liu, Xiaoying; Schneider, Daniel; Nestler, Britta
Abstract: With all the great advances in phase-field modelling combined with continuum mechanics, a detailed accuracy and convergence analysis about the influence of the diffuse interface upon the dynamic mechanical energy is still missing. Based on the previous work, i.e. deriving the homogenization scheme on the basis of balance conditions and embedding the high-order discontinuous Galerkin method into the phase field method, the influence of the diffuse interface, especially the multiphase/multigrain interface, on the dynamic mechanical energy is studied by considering the factors, such as the wave types, the material properties, the phase/grain size, the interface width and the normal vector formula. The numerical results are compared with the sharp-interface results to show the accuracy and stability, and with the linear homogenization method to demonstrate the advantages of the proposed scheme. The research work in this paper will build the foundation for the future simulation of rapid solid phase transformation. Highlights: The proposed homogenization scheme and the normal vector formulas are investigated. The results verify the numerical accuracy and stability of the proposed scheme. The proposed scheme shows its advantages over linear homogenization method. This paper builds a foundation for mechanical-wave-related microstructural analysis.